Inland desalination and concentrate management - He, Charlie (Qun); Bond, Rick G. (American Water Works Association, 2019)
As desalination technologies advance and the availability of conventional freshwater sources decreases, inland water users are increasingly turning to desalination. This manual presents the key issues and challenges of developing inland desalination facilities, including concentrate management and disposal methods.
Keywords: Saline water conversion.; elektronické knihy; electronic books